1997
DOI: 10.1136/gut.40.3.356
|View full text |Cite
|
Sign up to set email alerts
|

Detection and monitoring of serum p53 antibodies in patients with colorectal cancer.

Abstract: Background-Detection of p53 antibodies in serum might be an effective indirect procedure to detect alterations of the p53

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
43
2
2

Year Published

1999
1999
2008
2008

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(55 citation statements)
references
References 18 publications
8
43
2
2
Order By: Relevance
“…21,22 In the current study, the proportion (13%) of seropositive patients is consistent with a previous report on CRC 15 but represents a lower figure than other studies reporting positivity rates varying from 18 to 32%. 16,18,20,[23][24][25] In a previous study, 26 we reported that Taiwan had the lowest frequency of p53 mutations (31%) and the highest frameshift mutation rates among various population studies, which agrees with half of the CRC patients with a p53 mutation in the tumor having circulating p53-Abs. 3 In accordance with other studies, 18,23,25-27 in our series, we found no correlation with demographic or clinicopathologic features, except for tumor location and nodal status of the tumor.…”
Section: Discussionsupporting
confidence: 57%
“…21,22 In the current study, the proportion (13%) of seropositive patients is consistent with a previous report on CRC 15 but represents a lower figure than other studies reporting positivity rates varying from 18 to 32%. 16,18,20,[23][24][25] In a previous study, 26 we reported that Taiwan had the lowest frequency of p53 mutations (31%) and the highest frameshift mutation rates among various population studies, which agrees with half of the CRC patients with a p53 mutation in the tumor having circulating p53-Abs. 3 In accordance with other studies, 18,23,25-27 in our series, we found no correlation with demographic or clinicopathologic features, except for tumor location and nodal status of the tumor.…”
Section: Discussionsupporting
confidence: 57%
“…28 Therefore, it remains to be seen whether the intracellular antigens recognized by our phage antibodies are identical to the antigens described for the SEREX procedure. 37 Our data do not rule out the existence of humoral responses to certain cell surface antigens, as has been reported by others, 32,40,41 but they do show that there is a large bias toward intracellular 4,35,42,43 targets. It remains to be determined whether such epithelial cell-specific, somatically hypermutated antibodies are also found in other CRC patients.…”
Section: Discussioncontrasting
confidence: 42%
“…It has previously been shown that p53-Abs can be used for monitoring the follow-up of patients during therapy (Hammel et al, 1997;Polge et al, 1998;Zalcman et al, 1998). The presence of p73-Abs was tested in a series of patients for whom serum was available during therapy (data not shown, patients diffrent from those described in Table 1).…”
Section: P73 Antibodies and Follow-upmentioning
confidence: 99%